Peran Hukum Ekonomi Syariah Dalam Pembangunan Ekonomi Berkelanjutan - Calvin Alfiansyah; Fauzatul Laily Nisa (CV. KAMPUSA AKADEMIK PUBLISING, 2024)
This article examines the role of sharia economic law in the process of sustainable economic development. This research identifies how sharia economic principles such as the MAGRIB prohibition of justice and balance can play a role in the process of sustainable economic development. This article highlights how sharia economics can empower the community's economy so that it can reduce barriers to financial access for underprivileged people. Furthermore, this research reviews the responsible and sustainable management of natural resources in accordance with sharia economic principles, namely balance. The role of Islamic banking and financial institutions which aim to improve people's welfare, economic income and quality of life is also explained in depth in this article. Furthermore, this article also discusses the challenges faced in implementing sharia economic law in sustainable economic development. The resulting conclusion shows that sharia economic law with its principles that prioritize justice, balance and sustainability is deemed more suitable to support sustainable economic development than conventional economics which only prioritizes economic growth without paying attention to balance and sustainability in the future.